Fenomena Strawberry Generation dan Relevansinya dalam Perspektif Kitab Syarh Nahju al-Balaghah: The Strawberry Generation Phenomenon and Its Relevance in the Perspective of Syarh Nahju al-Balaghah - Shafira, Elsa Balqis (El-Suffah: Jurnal Studi Islam, 2025)
This research discusses about the Strawberry Generation, which possesses potential and challenges in the development of civilization. The term "Strawberry Generation" refers to the characteristics of a strawberry fruit – appealing in appearance but also fragile. This term originated in Taiwan and later spread to mainland China and other Asian regions. The research employs an analytical-descriptive method, drawing from literary sources to support study data. Interestingly, the study contextualizes an expression from the book "Sharh Nahj al-Balagha," stating that children are created for their time. This expression is utilized by the author to substantiate the phenomenon of the Strawberry Generation and seek solutions to its issues. Factors which influencing the emergence of the Strawberry Generation encompass parenting styles, communication, technology, and sociocultural influences. On the positive side, the Strawberry Generation exhibits enthusiasm in facing challenges, possesses the ability to voice opinions, is responsive to changing times, and displays remarkable creativity. Their zeal in capitalizing on opportunities, overcoming obstacles, and creating novel solutions is of paramount importance. By comprehending the characteristics of this generation profoundly, we can positively support their development and assist them in realizing their full potential amidst an ever-changing world. Abstrak: Penelitian ini mengulas tentang Generasi Stroberi yang memiliki potensi dan tantangan dalam pembangunan peradaban. Istilah "Generasi Stroberi" merujuk pada karakteristik buah stroberi yang tampak menarik namun rentan rapuh. Istilah ini muncul di Taiwan, kemudian menyebar ke Tiongkok daratan dan wilayah lain di Asia. Metode penelitian yang digunakan ialah c dengan merujuk pada sumber-sumber pustaka untuk menunjang data-data studi. Menariknya, dalam penelitian ini berusaha mengkontekstualisasikan salah satu ungkapan dalam kitab Syarh Nahju al-Balaghah yang menyatakan bahwa anak-anak diciptakan untuk zamannya. Ungkapan ini penulis gunakan sebagai pendukung atas fenomena generasi stroberi serta mencari solusi atas problematika yang dialaminya. Faktor-faktor yang mempengaruhi kemunculan Generasi Stroberi termasuk pola asuh, komunikasi, teknologi, dan pengaruh sosial budaya. Hingga sisi positif Generasi Stroberi seperti antusiasme dalam menghadapi tantangan, memiliki kemampuan berpendapat, responsif terhadap perubahan zaman, dan kreativitas yang luar biasa. Semangat mereka dalam memanfaatkan peluang, mengatasi hambatan, dan menciptakan solusi baru sangat penting. Dengan pemahaman yang mendalam tentang karakteristik generasi ini, kita dapat mendukung perkembangan mereka secara positif dan membantu mereka meraih potensi penuh mereka dalam menghadapi dunia yang terus berubah.